Retrofitting to Last – Selecting Optimal Wildlife Protection Products - Richard E. Harness; Duncan Eccleston (Пернатые хищники и их охрана)
Many power pylons in raptor habitat pose high electrocution risk to raptors, which can be mitigated with insulation products. Retrofitting may require a service outage and can be expensive; labor costs are often far greater than materials. Because concrete, steel and wood pylons often last for 50 years or more, utilities that select high quality raptor mitigation products receive much greater yield on their investment.